Actividad antimicrobiana de germicidas halogenados frente a aislamientos hospitalarios - Magariños, María del Carmen (2001)
Antiseptics and disinfectants are extensively used in hospitals and health care settings for a variety of topical and hard-surface applications. In particular, they are essential part of infection control practices and in the prevention of nosocomial infections. Despite this, few is known about the mode of action of these biocides with respect to antibiotics. In general, the antimicrobial activity can be influenced by many factors such as formulation effects, presence of organic matter, synergy, temperature, dilution and test method. The widespread use of antiseptics and disinfectant products has prompted some speculation on the development of microbial resistance, in particular cross-resistance to antibiotics. The aim of this study was to evaluate microbiological resistance to halogenated compounds by studying the behaviour of the grampositive and gramnegative clinical isolates against halogenated biocides usually applied, with and without organic substance and applying distilled water, potable water and water of 300 ppm hardness as dilution means. The results indicate that the hospital microorganisms show a higher resistance to the biocides than the strain Staphylococcus aureus ATCC 6538, although the effective concentration in clean conditions was lesser than the recommended ones, for all the dilution means. In presence of organic matter the antimicrobial activity was reduced in accordance with the bactericidal concentration of each microorganisrn, due to the oxidant action of these disinfectants